Face-to-face communication over the internet emotions in a web of culture, language, and technology - Kappas, Arvid; Krämer, Nicole C. (Studies in Emotion and Social Interaction, 2011)
"Social platforms such as MySpace, Facebook and Twitter have rekindled the initial excitement of cyberspace. Text based computer-mediated communication has been enriched with face-to-face communication such as Skype, as users move from desk tops to laptops with integrated cameras and related hardware. Age, gender and culture barriers seem to have crumbled and disappeared as the user base widens dramatically. Other than simple statistics relating to e-mail usage, chatrooms and blog subscriptions, we know surprisingly little about the rapid changes taking place. This book assembles leading researchers on non-verbal communication, emotion, cognition and computer science to summarize what we know about the processes relevant to face-to-face communication as it pertains to telecommunication, including video-conferencing. The authors take stock of what has been learned regarding how people communicate, in person or over distance, and set the foundations for solid research helping to understand the issues, implications and possibilities that lie ahead"--Provided by publisher